Estimating Each Other's Memory Biases in Dialogue. Issue 2 (7th February 2021) - Knutsen, Dominique; Le Bigot, Ludovic
ABSTRACT: Conversational memory is subject to a number of biases. For instances, references which were reused during dialogue are remembered better than non-reused references. Two experiments examined whether speakers are aware that they are subject to such biases and whether they use information about reference origin (i.e., information about who said what) to determine which references are remembered better by their partner. Pairs of participants performed a map task followed by a questionnaire that assessed each participant's content memory as well as each participant's estimation of his or her partner's memory. In Experiment 1, the participants were unaware that they would perform a memory test after the map task, whereas the participants were mutually aware of the upcoming memory test in Experiment 2. The results revealed that participants did know that their partner was subject to memory biases and that their estimation of these biases was mainly accurate. The results prevented us from drawing any conclusions about the role of origin memory in this process. These results have important implications for subsequent dialogic partner-adaptation.